1999
DOI: 10.1897/1551-5028(1999)018<2696:rdopbi>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Dechlorination of Polychlorinated Biphenyls: Interactions of Dechlorinating Microorganisms With Methanogens and Sulfate Reducers

Abstract: Abstract-The potential role of methanogens and sulfate reducers in polychlorinated biphenyl (PCB) dechlorination was investigated using the specific inhibitors 2-bromoethanesulfonate for methanogens and molybdate for sulfate reducers and the most probable number technique. Sediments were spiked with Aroclor 1248 (300 g/g). The inhibition of sulfate reducers did not have any effect on Aroclor 1248 dechlorination or on the size of dechlorinating populations, which indicates that they were not directly involved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 0 publications
2
22
2
Order By: Relevance
“…This hypothesis is also supported by the results of our recent work performed on another sediment of the same area of the Venice Lagoon (Fava et al 2003b). However, it cannot be totally excluded that methanogenic bacteria were involved in the process, as it has been reported for other marine sediments (Alder et al 1993), or that it was mediated by either sulfate-reducing and methanogenic bacteria along with fermentative bacteria, as it has been observed in other circumstances (Kim & Rhee 1999;Wiegel & Wu 2000).…”
Section: Biotransformation Of Weathered Pcbs In the Nonspiked Microcosmsmentioning
confidence: 84%
“…This hypothesis is also supported by the results of our recent work performed on another sediment of the same area of the Venice Lagoon (Fava et al 2003b). However, it cannot be totally excluded that methanogenic bacteria were involved in the process, as it has been reported for other marine sediments (Alder et al 1993), or that it was mediated by either sulfate-reducing and methanogenic bacteria along with fermentative bacteria, as it has been observed in other circumstances (Kim & Rhee 1999;Wiegel & Wu 2000).…”
Section: Biotransformation Of Weathered Pcbs In the Nonspiked Microcosmsmentioning
confidence: 84%
“…The predominant archaeal clone 1A and the exclusive archaeal groups 214A and 308A are nearly identical to Methanosarcina barkeri (98~99% identity). There is evidence that methanogens may play a role in certain meta dechlorinations (Chang et al, 1994;Kim and Rhee, 1999;Ye et al, 1999). A second methanogen group was identified in our RFLP analysis.…”
Section: J Microbiolmentioning
confidence: 99%
“…Our microcosm studies conducted with inocula from the St. Lawrence River sediment, which is primarily contaminated with Aroclor 1248, have demonstrated that there are at least two populations with different dechlorinating competence (Sokol et al, 1998;Kim and Rhee, 1999;Cho et al, 2000). When methanogens were inhibited with 2-bromoethanesulfonate (BES) in sediments amended with Aroclor 1248, the extent of dechlorination by St. Lawrence River sediment microorganisms was reduced by about half, indicating that some methanogens are involved in PCB dechlorination (Kim and Rhee, 1999). Using a combination of the dilution fractionation and most probable number (MPN) technique, we were able to distinguish populations of different competence and also quantify the population size (Cho et al, 2000).…”
mentioning
confidence: 95%
“…Previous studies indicate a positive influence of methanogens on anaerobic dechlorination of chloroethenes (7,20,43), polychlorinated biphenyls (30), and chloroform (55). However, the underlying processes are often poorly understood or are related to nondehalorespiratory mechanisms such as oxidative acetogenesis of VC (6,8) or beneficial influence of cofactors such as F430 and vitamin B 12 (55), which are involved in cometabolic reductive dechlorination (26).…”
mentioning
confidence: 99%